ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA ABK (SLOW LEARNER) PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Hotimah, Cindi Rahma; Lukman Hakim, Dori (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This article aims to determine the mathematical representation ability of students with special needs with the type of slow learner on variable linear equation system material at the junior high school level grade VIII Syech Quro at SMPI Al – Mumtaaz. The method used in this article is descriptive qualitative with the analysis used in this study is descriptive analysis on slow learners in the class. The population and sampling technique for this article is using the Purposive Sampling technique which uses a sampling technique with certain considerations, namely choosing 3 students including 2 boys and 1 girl. To demonstrate students' ability to represent story problems from the Two Variable Linear Equation System into mathematical and graphic forms.